Possibilities to enhance efficiency and durability of antimicrobial acne therapy in standard schemes of treatment - S. S. Ledentsova; P. V. Seliverstov; S. I. Sitkin; V. G. Radchenko (Лечащий Врач, 2021)
The article presents the results of a study on the effectiveness and tolerance of the preparation of butyric acid and inulin in patients with acne of moderate severity in standard treatment regimens.